CBP/p300 bromodomains regulate amyloid-like protein aggregation upon aberrant lysine acetylation - Olzscha, H; Fedorov, O; Kessler, B; Knapp, S; La Thangue, N (Cell Press, 2016)
Lysine acetylation is becoming increasingly recognized as a general biological principle in cellular homeostasis, and is subject to abnormal control in different human pathologies. Here, we describe a global effect on amyloid-like protein aggregation in human cells that results from aberrant lysine acetylation. Bromodomain reader proteins are involved in the aggregation process and, using chemical biology and gene silencing, we establish that p300/CBP bromodomains are necessary for aggregation to occur. Moreover, protein aggregation disturbs proteostasis by impairing the ubiquitin proteasome system (UPS) and protein translation, resulting in decreased cell viability. p300/CBP bromodomain inhibitors impede aggregation, which coincides with enhanced UPS function and increased cell viability. Aggregation of a pathologically relevant form of huntingtin protein is similarly affected by p300/CBP inhibition. Our results have implications for understanding the molecular basis of protein aggregation, and highlight the possibility of treating amyloid-like pathologies and related protein folding diseases with bromodomain inhibitor-based strategies.